1979
DOI: 10.1103/physrevlett.43.590
|View full text |Cite
|
Sign up to set email alerts
|

Critical Phenomena in Fluid Films: Scaling Crossover and Law of Corresponding States

Abstract: Thirty-two coexistence curves were measured for films of a critical mixture of 2, 6-lutidine +water for film thicknesses 0.46 //m ^L^ 14 ^m. For a sample of twenty-eight films with L <6 jum, the coexistence curves show a crossover from three-dimensional scaling characterized by i3«0.332 ±0.003 to two-dimensional Ising-model scaling with/3=0 0.126 ±0.005. The scaling requirement that a law of corresponding states exists for such filmxS has been confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The phase behavior of mixtures in thin films can be significantly different from the bulk [3][4][5][6][7][8][9][10][11][12][13][14]. Fisher et al theoretically considered an incompressible fluid mixture which interacted with isotropic nearest neighbor forces and showed that confinement only stabilized the single phase [4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phase behavior of mixtures in thin films can be significantly different from the bulk [3][4][5][6][7][8][9][10][11][12][13][14]. Fisher et al theoretically considered an incompressible fluid mixture which interacted with isotropic nearest neighbor forces and showed that confinement only stabilized the single phase [4][5][6][7].…”
mentioning
confidence: 99%
“…Experiments, however, show that, depending on the surfaces, confinement can either stabilize or destabilize the single phase relative to the bulk [9][10][11][12]. Since the model of Fisher corresponds to the simplest case of a binary fluid with isotropic nearest neighbor forces, a model with more complex interactions could rationalize the experiments [7].…”
mentioning
confidence: 99%
“…Computer simulation studies on confined lattice models [17] show the appearance of surface transitions in a range of temperatures below the LCSP. The same mechanism has been invoked to explain some experiments [18,19] that seemed to contradict the Nakanishi-Fisher picture.…”
Section: Introductionmentioning
confidence: 60%
“…However, this mechanism becomes inefficient for the capillary transition when the surface-to-volume ratio is small, and consequently we doubt that it can explain the experimental results in Refs. [18,19], which would correspond to the latter case. The disagreement with the scaling predictions in the cases in which the temperature shift depends on the substrate remains, in any case, unsolved.…”
Section: Discussionmentioning
confidence: 94%
“…In the limit L → ∞ we show that the bulk behavior is recovered and all corrections tend to zero. Contrarily, in the limit L → 0 we demonstrate how the "dimensional crossover" [4,22,23] shows up, overcoming the bulk behavior through non-trivial surface left-over, entirely out of bulk fields. Differently from previous approaches, the appearance of surface effects is due neither to the presence of interfaces between two materials (or the same material in different structural phases) nor the presence of external surface fields.…”
Section: Introductionmentioning
confidence: 71%